Comparison of Bone Loss around Bone Platform Shift and Non-Bone Platform Shift Implants After 12 Months - Amir Reza Rokn; Samareh Badri; Amir Alireza Rasouli Ghahroudi; Rebeca Manasheof; Mohamad Javad Kharazi Fard; Hamidreza Barikani (Tehran University of Medical Sciences, 2015)
Objectives: The aim of the present randomized clinical trial was to evaluate marginal bone loss around two types of implants modified at the neck area: Nobel Active and Nobel Replace Groovy, both manufactured by Nobel Biocare. Materials and Methods: A total of 25 Nobel Active and 21 Nobel Replace Groovy implants were included in the present study. The implants were placed based on the relevant protocol and patient inclusion and exclusion criteria. The amount of bone loss around implants was compared at 6 and 12-month intervals using digital periapical radiographs. Results: The mean bone loss values in the Nobel Active and Nobel Replace Groovy groups were 0.682 mm and 0.645 mm, respectively, with no statistically significant difference based on the results of independent t-test (P=0.802). Conclusion: Use of both implant types yielded favorable results, with high durability.The two implant types exhibited no superiority over each other in terms of bone loss.